Dynamics of the development of live weight in cows of the Kholmogory breed according to the polymorphism of the leptin gene - Natalуa A. Khudyakova; Irina S. Kozhevnikova; Alexsandra O. Stupina; Inga A. Klassen; Andrej S. Kashin (Аграрная наука Евро-Северо-Востока)
To improve the efficiency of dairy production, it is necessary to pay attention to the quality of rearing young cattle the growth and development of which depend not only on paratypical, but also on genetic factors. The research goal of the work was to identify the relationship between the leptin gene type (site A80V) and changes in live weight indicators in cows of the Kholmogory breed at different age periods. The studied livestock included 330 cows of the Kholmogory breed from the Arkhangelsk region. The whole blood was used as biomaterial. The results were visualized by electrophoresis in 2 % agarose gel with a molecular weight marker Step50 (Biolabmix LLC, Russia). The results of the study showed the predominance of carriers of the A allele, therefore, the AA genotype was the most common. Animals with the AV genotype had the highest weight gain over 6, 10, 12 and 18 months. The age of the first insemination, the first calving and the first fruitful insemination did not differ significantly. However, significant differences in live weight were found at the first insemination between groups with AV and VV genotypes (+16.94 kg), as well as between animals with AA and VV genotypes (+15.49 kg). The average weight gain per month was also higher in animals with the AV genotype (+18.03±0.31 kg). It has been established that the most preferred genotype of the leptin gene of the A80V site in the sample of cows of the Kholmogorsky breed is the AV genotype. The further study of the leptin gene and its effects will help to gain a more complete understanding of its role in shaping the growth of living tissue in animals.